Perancangan Sistem Informasi Permohonan Cuti Berbasis Website - Yahfizham Yahfizham; Sahnas wulandari Siregar; Yolanda Sianturi (Lembaga Pengembangan Kinerja Dosen, 2024)
All agency employees have the right to take leave, which is one of their rights and obligations. Many companies still carry out employee leave manually. TELKOM MEDAN VOCATIONAL SCHOOL still uses letters to process employee data. To overcome this problem, an information system was created to manage employee leave. With the Website-Based Employee Leave Application Information System at TELKOM MEDAN Vocational School, designing this website consists of several stages, including interviews, data collection, and data analysis observation. Then, using UML, each component is designed and analyzed.